Respuesta :

Answer:

Final answer is [tex]3+4\ln(x)[/tex]

Step-by-step explanation:

Given expression is [tex]\ln(e^3x^4)[/tex], where x>0

Now we need to simplify that expression.

Apply formula [tex]\ln(AB)=\ln(A)+\ln(B)[/tex]

[tex]=\ln(e^3)+\ln(x^4)[/tex]

Apply formula [tex]\ln(x^m)=m\ln(x)[/tex]

[tex]=3\ln(e)+4\ln(x)[/tex]

Apply formula [tex]\ln(e)=1[/tex]

[tex]=3(1)+4\ln(x)[/tex]

[tex]=3+4\ln(x)[/tex]

Hence final answer is [tex]3+4\ln(x)[/tex]

Answer:

3+4 in x

Step-by-step explanation: